Leisure Class Dalam Pola Konsumsi Mahasiswa UIN Alauddin Makassar: Leisure Class in the Consumption Patterns of UIN Alauddin Makassar Students - Mala, Nur; Sirojuddin; Muslihati (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
This study examines the leisure class phenomenon in the consumption patterns of UIN Alauddin Makassar students, focusing on the tendency of excessive consumption that prioritizes desires over needs. This phenomenon shows the existence of consumptive behavior that is inseparable from the influence of the social environment, lifestyle, and increasingly rapid technological developments. The purpose of this study is to analyze in more depth how the leisure class is formed and influences students' consumption patterns in their daily lives. The research method used is a qualitative approach with a phenomenological research type. The results of the study indicate that (1) the excessive consumption pattern in the leisure class is supported by factors of social class, lifestyle, personality and self-concept, as well as the difference between desires and needs; (2) factors that influence the formation of the leisure class include parental income, taste in technology, and product quality; (3) the impacts of the leisure class consumption pattern include wasteful behavior and the emergence of social jealousy among students; (4) when viewed from the concept of consumption according to Imam Al-Ghazali, the student consumption pattern is classified as excessive and exceeds the limits of needs. Therefore, this study recommends that students be wiser in regulating consumption patterns by prioritizing needs over desires alone in order to avoid the negative impacts that arise.